1564. Activity of bacteriophage against multidrug resistant Klebsiella pneumoniae. (31st December 2020) - Puttagunta, Sailaja; Kahan-Haanum, Maya; Kredo-Russo, Sharon; Weinstock, Eyal; Khabra, Efrat; Edgar, Rotem; Weiner, Iddo; Ben-Ishay, Noa; Eyal, Stav; Inbar, Dana; Puri, Doron; Kaikov, Dana; et al.
Abstract: Background: The prevalence of extended-spectrum beta-lactamase (ESBL) producing and carbapenem resistant (CR) Klebsiella pneumoniae (KP) has significantly risen in all geographic regions. Infections due to these bacteria are associated with high mortality across different infection types. Even with newer options, there remains an unmet need for safe and effective therapeutic options to treat infections caused by ESBL and CR KP . Phage therapy offers a novel approach with an unprecedented and orthogonal mechanism of action for treatment of diseases caused by pathogenic bacterial strains that are insufficiently addressed by available antibiotics. Phage-based therapies confer a high strain-level specificity and have a strong intrinsic safety profile. Here we describe the identification of novel phages that can effectively target antibiotic resistant KP strains. Host range of the 21 phages on 33 strain KP panel via solid culture infectivity assays. Red marks resistance to infection while sensitivity to phage is marked in green Methods: KP clinical strains were isolated from human stool specimens preserved in glycerol. Selective culturing was carried, followed by testing of individual colonies for motility, indole and urease production, sequenced and analyzed by Kleborate tool to determine antibiotic resistant genes. Natural phages were isolated from plaques that developed on susceptible bacterial targets, sequenced and characterized. Results: Antibiotic-resistant KP strains encoding beta lactamase genes or a carbapenemase (n=33) were isolated from healthy individuals (n=3), and patients with inflammatory bowel disease (n=26) or primary sclerosing cholangitis (n=3). Isolates sequencing revealed bla CTX-M15 and/or bla SHV encoding strains and carbapenamase KPC-2. A panel of 21 phages targeting the beta-lactamase- and carbapenemase-producing KP strains were identified. Phage sequencing revealed that all phages belong to the Caudovirales order and include 6 Siphoviridae, 14 Myoviridae, and 1 Podoviridae. In vitro lytic activity of the phages was tested on the isolated bacteria and revealed a coverage of 70% of the 33 isolated antibiotic resistant strains, >50% of which were targeted by multiple phages. Conclusion: Collectively, these results demonstrate the feasibility of identifying phage with potent activity against antibiotic resistant KP strains, and may provide a novel therapeutic approach for treatment of ESBL and CR KP infections. Disclosures: All Authors : No reported disclosures